Answer:
15
Step-by-step explanation:
To solve this, divide 192 by 8:
192/9 = 24
Subtract 9 from 24:
24 - 9 = 15
Therefore, 8 times the sum of 9 and 15 is 192
It is Rong the answer is 2
Answer:
4(2e - 3)(3e + 1)
Step-by-step explanation:
Given
24e² - 28e - 12 ← factor out 4 from each term
= 4(6e² - 7e - 3) ← factor the quadratic
Consider the factors of the product of the e² term and the constant term which sum to give the coefficient of the e- term.
product = 6 × - 3 = - 18 and sum = - 7
The factors are - 9 and + 2
Use these factors to split the e- term
6e² - 9e + 2e - 3 ( factor the first/second and third/fourth terms )
= 3e(2e - 3) + 1 (2e - 3) ← factor out (2e - 3) from each term
= (2e - 3)(3e + 1)
Then
24e² - 28e - 12 = 4(2e - 3)(3e + 1) ← in factored form
Answer:
The answer is -40
Step-by-step explanation:
<h3><u>Given</u>;</h3>
<h3><u>To </u><u>Find</u>;</h3>
Now,
a – 5y
(-5) – 5(7)
-5 – 35 = -40
Thus, The answer is -40
<u>-TheUnknownScientist</u><u> 72</u>